Long Term Exposure to Tenofovir Disoproxil Fumarate-Containing Antiretroviral Therapy Is Associated with Renal Impairment in an African Cohort of HIV-Infected Adults. (22nd January 2019) - Agbaji, Oche O.; Abah, Isaac O.; Ebonyi, Augustine O.; Gimba, Zumnan M.; Abene, Esla E.; Gomerep, Simji S.; Falang, Kakjing D.; Anejo-Okopi, Joseph; Agaba, Patricia A.; Ugoagwu, Placid O.; Agaba, Emmanuel I.; Imade, Godwin E.; et al.
Objectives and Method: There are growing concerns of tenofovir disoproxil fumarate (TDF)–associated renal toxicity. We evaluated the effect of long-term TDF exposure on renal function in a cohort of HIV-1-infected Nigerians between 2006 and 2015. Multivariate logistic regression was used to identify predictors of renal impairment at different time over 144 weeks of antiretroviral therapy (ART). Results: Data of 4897 patients, median age 42 years (interquartile range: 36-49), and 61% females were analyzed. The prevalence of renal impairment increased from 10% at week 24 to 45% at 144 weeks in TDF-exposed participants compared to an increase from 8% at 24 weeks to 14% at 144 weeks in TDF-unexposed participants. Tenofovir disoproxil fumarate exposure predicted the risk of renal impairment at 144 weeks of ART (odds ratio: 2.36; 95% confidence interval: 1.28-4.34). Conclusion: Long-term exposure to TDF-based ART significantly increases the likelihood of renal impairment. The continued use of TDF-based regimen in our setting should be reviewed. We recommend the urgent introduction of tenofovir alafenamide–based regimen in the HIV treatment guidelines of Nigeria and other resource-limited countries.